2021
DOI: 10.3390/ijms22052783
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Cellular Targets of Particulate Matter

Abstract: Particulate matter (PM) is constituted by particles with sizes in the nanometer to micrometer scales. PM can be generated from natural sources such as sandstorms and wildfires, and from human activities, including combustion of fuels, manufacturing and construction or specially engineered for applications in biotechnology, food industry, cosmetics, electronics, etc. Due to their small size PM can penetrate biological tissues, interact with cellular components and induce noxious effects such as disruptions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 121 publications
0
19
0
1
Order By: Relevance
“…The exact mechanism by which PEI activates TRPV1 receptors is presently unclear. Previous studies with silica nanoparticles (SiNPs) have suggested that cell surface perturbations resulting from SiNP particles striking the plasma membrane can produce TRPV1 activation by mechanical stimulation [54]. In contrast, insoluble electrophilic compounds present in coal fly ash particles activate TRPV1 through interactions with amino acids within the pore-loop region of the channel [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism by which PEI activates TRPV1 receptors is presently unclear. Previous studies with silica nanoparticles (SiNPs) have suggested that cell surface perturbations resulting from SiNP particles striking the plasma membrane can produce TRPV1 activation by mechanical stimulation [54]. In contrast, insoluble electrophilic compounds present in coal fly ash particles activate TRPV1 through interactions with amino acids within the pore-loop region of the channel [55].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, insoluble electrophilic compounds present in coal fly ash particles activate TRPV1 through interactions with amino acids within the pore-loop region of the channel [55]. Diesel exhaust particles can also open TRPV1 channels in epithelial cells by indirectly activating protease-activated receptor 2 (PAR2), resulting in Ca 2+ mobilization from internal stores, inflammatory mediator release and matrix metalloprotease activation [54]. Increasing extracellular concentrations of Na + , Mg 2+ , and Ca 2+ also opens TRPV1 channels expressed in HEK293 cells and oocytes presumably by interacting with two glutamate residues (E600 and E648) located near the pore region of the channel [56].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and toxicological studies show varying types and degrees of health effects related to PM, suggesting a role for both the chemical composition (such as transition metals and combustion-derived primary and secondary organic particles) and physical properties (size, shape, and surface area) along with concentration [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Yet, the research in this field is limited and controversial, particularly when comparing the results from epidemiological and experimental (in vivo and in vitro) studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent research has illustrated the importance of studying also the acute interaction of NPs with specific cellular structures and signaling pathways. For instance, NP-induced modulation in the time scales of seconds and minutes have been reported for cation-permeable channels that play crucial roles in cell signaling [30][37] [39][41] [42]. In this sense, ATP-mediated signaling is considered to be involved in inflammatory responses to NPs in multiple cell types [43][44][45][46][47] [48].…”
Section: Introductionmentioning
confidence: 99%